Investigation of natural hybrid sandwich panel and thin skin cover towards acoustical performance - Balakrishnan, Paramananthan (2019)
Sandwich structure is a very expensive engineering material. However, due to its multiple advantages such as light weight and high strength, its demand is relatively high. In this project, the natural material fiber was intended to replace the synthetic fiber in the core to reduce its dependency on synthetic materials. Basically, the use of natural material can minimize the cost in terms of materials and processing as well as to conserve the environment by reducing the waste of natural material. This research utilized the green natural fiber in the manufacturing of acoustic panel which must own good behavior such as the sound absorption. Furthermore, the materials and the processes involve are simple and cost effective. The materials used were coconut fiber, polystyrene, polyurethane, and polyester. The sandwich structure was done by using hand lay-up and press technique using a hydraulic press machine with 1 ton pressure. The natural acoustic panel is drilled in order to produce perforation on the surface of the panel. The parameter used in this research is the perforation of the natural fiber. The suggested diameter for the perforation is 3 mm and 6 mm. The acoustical behavior of the sandwich structure was tested by using impedance tube test. There are 23 sample designs for the core and 18 samples for the skin cover were prepared for the impedance tube testing. The impedance tube testing was used to measure the absorption coefficient of the natural fiber. Among the 23 samples that had been tested, the most suitable sample to be applied as an acoustic panel at low, medium and high frequency were S3, S13 and S14, respectively. In particular, 0.90, 0.98 and 0.85 of the absorption coefficient value at 600, 1500 and 2400 Hz, respectively. There is no or less research and testing done for the skin material. The suggested skin material also serves as a decorative and protective layer for the core or acoustic panel. The proposed material which is the cotton material with 2 layers of the same material with an 10 mm air gap in between the 2 layers and 10 mm gap to the core was recommended to be used as skin material for an acoustic core panel as the material had a very good sound absorption coefficient.